Effect of ascorbic acid on chemical content and viability of cocoa seed after storage - Willy Daniel Sekewael; Endang Pudjihartati; Teguh Iman Santoso (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2019)
Storage of oily seeds will make the seeds deteriorated, this caused by auto-oxidation. It will changes the biochemical and physiology of the seeds. Application of Antioxidant can prevent the activity of auto-oxidation. This research aimed to study the effect of ascorbic acid to minimize the deterioration by observing the chemical content and viability of Theobroma cacao L. seeds. It was conducted at kaliwining experimental station, Indonesia Coffee and Cocoa Research Institute, Jember, East Java and at Universitas Kristen Satya Wacana, Salatiga, Central Java. The research used Completely Randomized Design and T-test analysis. The treatments consisted of four ascorbic acid concentrations, i.e. 0 ppm as control, 250 ppm, 300 ppm, and 350 ppm. The treated cacao seeds were stored on two shelf life i.e. 1 week and 2 weeks. Each treatment was repeated with seven replications. Data analysis used SAS 9.0. The results showed that ascorbic acid application can effect on reducing sugar, protein, lipid, free fatty acid content, and viability of cocoa seeds. Ascorbic acid with concentration of 250 ppm and 300 ppm can maintain cocoa seeds viability until 2 weeks of shelf life.